Oxidation decomposition mechanism of fluoroethylene carbonate-based electrolytes for high-voltage lithium ion batteries: a DFT calculation and experimental study - Xia, Lan; Tang, Bencan; Yao, Linbin; Wang, Kai; Cheris, Anastasia; Pan, Yueyang; Lee, Saixi; Xia, Yonggao; Chen, George Z.; Liu, Zhaoping (Wiley, 2017)
The oxidative decomposition mechanism of fluoroethylene carbonate (FEC) used in high-voltage batteries is investigated by using density functional theory (DFT). Radical cation FEC•+ is formed from FEC by transferring one electron to electrode and the most likely decomposition products are CO2 and 2-fluoroacetaldehyde radical cation. Other possible products are CO, formaldehyde and formyl fluoride radical cations. These radical cations are surrounded by much FEC solvent and their radical center may attack the carbonyl carbon of FEC to form aldehyde and oligomers of alkyl carbonates, which is similar with the oxidative decomposition of EC. Then, our experimental result reveals that FEC-based electrolyte has rather high anodic stability. It can form a robust SEI film on the positive electrode surface, which can inhibit unwanted electrolyte solvent and LiPF6 salts decomposition, alleviate Mn/Ni dissolution and therefore, improve the coulombic efficiency and the cycling stability of high voltage LiNi0.5Mn1.5O4 positive electrodes. This work displays that FEC-based electrolyte systems have considerable potential replacement of the EC-based electrolyte for the applications in 5 V Li-ion batteries.